2019
DOI: 10.1186/s12931-019-1047-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of airway tree to lung volume ratio on computed tomography with lung function and symptoms in chronic obstructive pulmonary disease

Abstract: Background Decreased airway lumen size and increased lung volume are major structural changes in chronic obstructive pulmonary disease (COPD). However, even though the outer wall of the airways is connected with lung parenchyma and the mechanical properties of the parenchyma affect the behaviour of the airways, little is known about the interactions between airway and lung sizes on lung function and symptoms. The present study examined these effects by establishing a novel computed tomography (CT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 45 publications
(54 reference statements)
1
34
1
Order By: Relevance
“…Dysanapsis refers to a mismatch of airway tree caliber to lung size and was initially inferred from variation in spirometry among healthy adults. 11 Dysanapsis is believed to arise early in life, 11 has been implicated in obstructive lung disease susceptibility, 12,13 and can be quantified directly using computed tomography (CT). 14 This study examined the hypothesis that dysanapsis quantified by CT as the ratio of mean airway lumen diameter to total lung volume (airway to lung ratio) would statistically account for a significant proportion of the variation in forced expired volume in the first second to forced vital capacity (FEV 1 :FVC) ratio, and be associated with incident COPD among older adults in the general population.…”
mentioning
confidence: 99%
“…Dysanapsis refers to a mismatch of airway tree caliber to lung size and was initially inferred from variation in spirometry among healthy adults. 11 Dysanapsis is believed to arise early in life, 11 has been implicated in obstructive lung disease susceptibility, 12,13 and can be quantified directly using computed tomography (CT). 14 This study examined the hypothesis that dysanapsis quantified by CT as the ratio of mean airway lumen diameter to total lung volume (airway to lung ratio) would statistically account for a significant proportion of the variation in forced expired volume in the first second to forced vital capacity (FEV 1 :FVC) ratio, and be associated with incident COPD among older adults in the general population.…”
mentioning
confidence: 99%
“…Notably, the multivariate analysis showed that the increase in AWV% was associated with the improvement in FEV1 independently of the changes in TAC. A previous study showed that while AWV% reflects the dimension of the central airways and TAC on CT, AWV% is associated with airflow limitation and gas trapping independent of emphysema, the dimension of the central airway, and TAC (Tanabe et al, 2019); furthermore, the study suggested that in addition to each structural change in the airway and lung, the interaction between airway and lung volumes would affect pulmonary function. Taken together, the present results suggest that LAMAs work by increasing the lumen diameter of the airways identifiable on the baseline CT scan and the number of airways in the lower lobe identifiable on the follow-up CT scan, which could reverse the ratio of the disproportionately small airway lumen volumes to the relatively large lung and might mechanistically improve breathing efficiency.…”
Section: Discussionmentioning
confidence: 87%
“…The details of the calculation method for AWV% were recently reported (Tanabe et al, 2019). Briefly, the segmentation of the airway tree was automatically generated without any manual editing using a SYNAPSE VINCENT volume analyser (FUJIFILM Medical).…”
Section: Ct Measurementsmentioning
confidence: 99%
See 2 more Smart Citations